Sei sulla pagina 1di 9

Cambridge Physics PhD Tutor IB DSE IGCSE SAT

hinwahk@gmail.com
UC Math MA, HKU Chemist 93197825 AP MCAT GCE
HKU 1st Hons Engineer

Steps for integration by substitution.

Step 1: Choose a new variable u

Step 2: Determine the value dx

Step 3: Make the substitution

Step 4: Integrate resulting integral

Step 5: Return to the initial variable x

(ln x) 4
Example 1 Find  x dx .

Solution 1:
1
Let u = lnx, then du = d(lnx) = dx .
x
4 1 
4
(ln x)
  x dx =  (ln x)  x dx 
=  u 4 du
1
= u5 + C
5
1
= (ln x) 5 + C
5

(ln x) 4
Solution 2:  x dx =  (ln x) d ln x
4

1
= (ln x) 5 + C
5
Integration by substituting u = ax + b

Example 2: Evaluate  (2 x + 3)
4
dx

Solution 1:

Step 1: Let u=2x+3


Step 2: Determine dx

Step 3: Make the substitution

Step 4: Integrate resulting integral

=
Step 5: Return to the initial variable x

1
Solution 2: (without letting u)  (2 x + 3) dx =
2
(2 x + 3) 4 d (2 x + 3)
4

1 (2 x + 3)5
= +C
2 5
(2 x + 3) 5
= +C
10

Solution 3: (expand by binomial theorem and integrate term by term)


15
Example 3: Evaluate  3 − 2 x dx

Solution:

Step 1: Let u=3-2x


Step 2: Determine the value dx

Step 3: Make the substitution

Step 4: Integrate resulting integral

Step 5: Return to the initial variable x

Thus,

Solution 2:

15
 3 − 2 x dx
− 1 15
2  3 − 2x
= d (3 − 2 x)

−1
= (15) ln 3 − 2 x + C
2
− 15
= ln 3 − 2 x + C
2
2x
Example 4 Evaluate x 2
+1
dx .

2x
Answer:  dx = ln( u ( x)) = ln( x 2 + 1).
x +1
2

Solution 1:

Let u = x 2 + 1 . Then
du
= 2 x  du = 2 xdx ,
dx
we get

2x 1
x 2
+2
dx =  du = ln( u ) = ln( x 2 + 1) + C
u

Solution 2:

2x d ( x 2 + 1)
 x 2 + 1 dx =  x 2 + 1 = ln(x + 1) +C
2

Example 5 Evaluate x x 2 + 3dx .

Solution 1:

Let u = x 2 + 3 , du = 2 xdx

1 1 1 12 1 2 32 1 2 3
 + =  2 =  = = + +C
2 2 2
x x 3dx u ( ) du u du ( )u ( x 3)
2 2 3 3

1 1 2 2 3 1 2 3
 x x + 3dx =  + + = + + = + +C
2 2 2 2 2
Solution 2: x 3d ( x 3) ( )( x 3) C ( x 3)
2 2 3 3
 3x 2 + 2 
    x3 + 2 x  dx
2
+1
Example 6 a) x 2 x 3 + 1 dx b) 4 xe2 x dx c)

du du
Solution: a) Let u = x3 + 1 . Then, = 3x 2 → du = 3x 2 dx → = dx
dx 3x 2

du
Substitute u for x3 + 1 and for dx.
3x 2

du
x x3 + 1 dx =  x 2 u
2

3x 2

1
= u du
3
1
 ( u ) 2 du
1
=
3
1 2 3 
=  u 2 +C
3 3 
2 3
= u 2 +C
9

(
2 3
x + 1) + C
3
2
=
9

b) Since f ( x) = 2 x 2 + 1 we let u = 2 x 2 + 1 and then differentiate both sides of the equation with respect to x

du du
= 4 x → du = 4 x dx → = dx .
dx 4x

du
 4 xe dx =  4 x eu =  eu du = eu + C = e2 x +1 + C
2 x 2 +1 2

4x

c) let u = x 3 + 2 x , then
du
dx
= 3x 2 + 2 → du = 3x 2 + 2 dx → ( ) du
3x 2 + 2
= dx

3x 2 + 2 du du
 u  3x 2 + 2 =  u = ln u + C = ln x + 2 x + C
3
xdx
Example 7 Find (a)  x( x + 1) dx , (b)  .
6
3
3x + 4

Solution:
(a) Let u = x + 1, then du = d(x + 1) = dx.
  x( x + 1) dx =  (u − 1)u 6 du
6

=  (u 7 − u 6 )du
1 1
= u8 − u7 + C
8 7
1 1
= ( x + 1)8 − ( x + 1) 7 + C
8 7
(b) Let u = 3x + 4, then du = d(3x + 4) = 3dx,
1 1
i.e. du = dx and x = (u − 4) .
3 3
1 1 
(u − 4) du 
xdx 3 3 
  3
3x + 4 
= 1
3
u
1
1 −
=
9
u 3
(u − 4)du
2 1
1 −
=
9
 (u 3
− 4u 3 )du

1  3 3 3 
5 2

= u −4• u3 +C
9  5 2 
5 2
1 2
= u3 − u3 +C
15 3
5 2
1 2
= (3x + 4) − (3x + 4) 3 + C
3
15 3
Example 8. Calculate the integral ∫ 2𝑥 𝑒 𝑥 𝑑𝑥..

Solution.

We rewrite the integral in the following way:

∫ 2𝑥 𝑒 𝑥 𝑑𝑥 = ∫ (2𝑒)𝑥 𝑑𝑥.

Denoting 2e=a2e = a (this is not a change of variable, since x still remains the independent
variable), we get the table integral:

𝑎𝑥 (2𝑒)𝑥 2𝑥 𝑒 𝑥 2𝑥 𝑒 𝑥
∫ (2𝑒)𝑥 𝑑𝑥 = ∫ 𝑎 𝑥 𝑑𝑥 = +𝐶 = +𝐶 = +𝐶 = + 𝐶.
ln 𝑎 ln(2𝑒) ln⁡ 2 + ln⁡ 𝑒 ln⁡ 2 + 1

sin 𝑥
Example 9. Evaluate the integral ∫ 𝑑𝑥.
1−cos⁡ 𝑥
Method 1
We make the substitution 𝑢 = 1 − cos⁡ 𝑥. Hence
𝑑𝑢 = −(− sin 𝑥)𝑑𝑥 = sin 𝑥𝑑𝑥.
This gives
sin 𝑥 𝑑𝑢
∫ 𝑑𝑥 = ∫ = ln⁡ |𝑢| + 𝐶 = ln⁡ |1 − cos⁡ 𝑥| + 𝐶.
1 − cos⁡ 𝑥 𝑢
Method 2
sin 𝑥 x
∫ 𝑑𝑥 = ∫ cot 𝑑𝑥
1 − cos 𝑥 2
x
cos 2
=∫ x 𝑑𝑥
sin 2

1 x
= 2∫ x 𝑑 sin 2
sin 2
x
= 2 ln⁡|sin | + 𝐾
2
Example 10. Evaluate the integral ∫ 𝑥 √𝑥 + 1𝑑𝑥.
Solution.
To get rid of the square root, we make the substitution 𝑢 = √𝑥 + 1. . Then
∫ 𝑥√𝑥 + 1𝑑𝑥 = ∫ (𝑢2 − 1)𝑢 ⋅ 2𝑢𝑑𝑢 = 2∫ (𝑢2 − 1)𝑢2 𝑑𝑢 = 2∫ (𝑢4 − 𝑢2 )𝑑𝑢 = 2∫ 𝑢4 𝑑𝑢 − 2∫ 𝑢2 𝑑𝑢
𝑢5 𝑢3 2 5 2 3
=2⋅ − 2 ⋅ + 𝐶 = (𝑥 + 1)2 − (𝑥 + 1)2 + 𝐶.
5 3 5 3

The integral becomes

∫ 𝑥√𝑥 + 1𝑑𝑥 = ∫ (𝑢2 − 1)𝑢 ⋅ 2𝑢𝑑𝑢 = 2∫ (𝑢2 − 1)𝑢2 𝑑𝑢 = 2∫ (𝑢4 − 𝑢2 )𝑑𝑢 = 2∫ 𝑢4 𝑑𝑢 − 2∫ 𝑢2 𝑑𝑢


𝑢5 𝑢3 2 5 2 3
=2⋅ − 2 ⋅ + 𝐶 = (𝑥 + 1)2 − (𝑥 + 1)2 + 𝐶.
5 3 5 3
Shortcut
∫ 𝑥√𝑥 + 1𝑑𝑥 = ∫ (𝑥 + 1 − 1)√𝑥 + 1𝑑(𝑥 + 1)
3 1
= ∫ ((𝑥 + 1)2 − (𝑥 + 1)2 ) 𝑑(𝑥 + 1)

2 5 2 3
= (𝑥 + 1)2 − (𝑥 + 1)2 + 𝐶
5 3

sin⁡ 2𝑥
Example 11. Find the integral ∫ 𝑑𝑥.
√1+cos2 𝑥

Solution.

We make the following substitution:

𝑢 = 1 + cos 2 𝑥, ⇒ 𝑑𝑢 = (1 + cos2 𝑥)′ 𝑑𝑥 = 2cos⁡ 𝑥 ⋅ (−sin⁡ 𝑥)𝑑𝑥 = −sin⁡ 2𝑥𝑑𝑥.

Hence,
sin⁡ 2𝑥 (−𝑑𝑢) 𝑑𝑢
∫ 𝑑𝑥 = ∫ = −2∫ = −2√𝑢 + 𝐶 = −2√1 + cos 2 𝑥 + 𝐶.
√1 + cos 2 𝑥 √𝑢 2√𝑢
Shortcut
sin 2𝑥 2 sin 𝑥 cos𝑥 1
∫ 𝑑𝑥 = ∫ 𝑑𝑥 = −∫ 𝑑cos 2 𝑥
√1 + cos 2 𝑥 √1 + cos2 𝑥 √1 + cos2 𝑥
−1
= −∫ (1 + cos 2 𝑥) 2 𝑑(1 + cos2 𝑥)

= −2√1 + cos 2 𝑥 + 𝐶
Your Turn!
(I) Worked example and exercises

 x(x )6
(i) Calculate 2
+ 1 dx.

1
( 1 6
) 1 u7 ( )
x2 +1
7

 2
6
Set u = x + 1 . Then du = xdx , so that
2
x x + 12
dx = u du = = .
2 2 7 14

(ii) Calculate  sin( x)(cos( x) + 3) dx.


5

x2
(iii) Calculate  3 dx .
x +1
ex +1
(iv) Calculate  x dx.
2e + 2 x
cos(2 x)
(v) Calculate  sin(2 x) + 3 dx.

(vi) x 2
x
+1
(
ln( x 2 + 1) − 2 )−3
dx.

3
x 2e x
(vii) e x3
+1
dx.

Q1. Evaluate each indefinite integral by method of substitutions:

 x (2 x + 3) dx
1 3
 x(ln x) dx e
5
(i) 2 3
(ii) (iii) dx
x
(1 − e − x )
x
3e 2 x ln x e
(iv)  2 x
e +1
dx (v)  x
dx (vi)  x
dx

7
e x
(vii)  2 dx
x
Q2. Evaluate each indefinite integral by method of substitutions:

 2 x(x + 2) dx x x
5
(i) (ii) 3
1 − x dx (iii) 2
1 − x dx

x +1
(iv)  x −1
dx